POLA ASUH ANAK DALAM KELUARGA ( Studi kasus pada pengamen anak-anak di kampung Jlagran, Yogyakarta ) - Puji Lestari * (Dimensia: Jurnal Kajian Sosiologi, 2008)
The research with the title ” Parenting Method in Family” (Case Study of Singing Beggar-Children in Jlagran)”, is held to learn the method of parenting which is applied by parent to children. This is to gain clear information on parenting which results child abuse and its psichological efect to children. Child abuse here is classified as physic, verbal and economic. This research is using the qualitative method emphasizing to the aspect of deeper information which is obtained by conducting interview and supported by field observation and documentation. 19 respondences which are 8 elders, 1o children and 1 Jlagran’s aboriginal were interviewed. The 8 elder people and 10 children are not Jlagran’s aboriginal. They live in a poor economic condition. Most of them rent house from Jlagran’s people however some also live in fabric and wood wall; attached to others. The research then resulting information that the parenting method of each family is varies to parent’s chararcter. This parenting method also brings different psichological effects to the children who mostly are singing beggars.With otoriter parent, children tend to live in fear, less confidence, full of anger and quite. This otoriter parenting form tends to give stress on violance. With permisive parenting method, children tend to turn to be wild due to lack of parent’s control. While only a small number of parents are applying the demoratic method where children’s life and their need to express are more accomodated. Keywords: Children;s Parenting Method, Family, Singing Beggar